Notes from a young Black chef - Onwuachi, Kwame; Stein, Joshua David (Delacorte Press, 2021)
"This inspiring memoir chronicles Top Chef star and Forbes and Zagat 30 Under 30 phenom Kwame Onwuachi's incredible--and odds-defying--rise to fame in the food world after a tough childhood in the Bronx and Nigeria. Young adult edition. [This work is based on Notes from a Young Black Chef: A Memoir, copyright © 2019 by Kwame Onwuachi. Published in hardcover by Alfred A. Knopf, an imprint of the Knopf Doubleday Publishing Group, a division of Penguin Random House LLC, New York, in 2019.]"--